2021
DOI: 10.3390/rs13091851
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Terrestrial Water Storage Changes with the Tongji-Grace2018 Model in the Nine Major River Basins of the Chinese Mainland

Abstract: Data from the Gravity Recovery and Climate Experiment (GRACE) satellite mission can be used to monitor changes in terrestrial water storage (TWS). In this study, we exploit the TWS observations from a new temporal gravity field model, Tongji-Grace2018, which was developed using an optimized short-arc approach at Tongji University. We analyzed the changes in the TWS and groundwater storage (GWS) in each of the nine major river basins of the Chinese mainland from April 2002 to August 2016, using Tongji-Grace2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Water scarcity is a key restriction on the sustainable development of agriculture in arid and semi-arid areas [27]. A suitable supply of water and nitrogen can maintain plant growth and development, increasing the functionality of the leaf stage and leaf area index.…”
Section: Response Of Winter Wheat Growth and Development To Water-nit...mentioning
confidence: 99%
“…Water scarcity is a key restriction on the sustainable development of agriculture in arid and semi-arid areas [27]. A suitable supply of water and nitrogen can maintain plant growth and development, increasing the functionality of the leaf stage and leaf area index.…”
Section: Response Of Winter Wheat Growth and Development To Water-nit...mentioning
confidence: 99%
“…The water hyacinth C/N ratio is approximately 20:1. Under anaerobic conditions, microorganisms can use their nutrients for the anaerobic fermentation of methane [35]. found that water hyacinths and other aquatic plants are able to be easily degraded.…”
Section: Biogasmentioning
confidence: 99%
“…GRACE data are processed by NASA to generate the Total Water Storage Anomaly (TWSa) dataset, which captures the change in water storage globally in an anomaly format [24]. GRACE data have been used for various applications, such as flood studies [25][26][27][28][29], drought studies [30][31][32][33][34][35], and general hydrologic investigations focusing on regional water storage and trends [36][37][38]. Recent research has demonstrated the use of GRACE data for monitoring variations in groundwater storage [39][40][41][42][43] including variations in groundwater depletion in arid and semiarid regions [15,44,45].…”
Section: Grace Datamentioning
confidence: 99%